การพัฒนาเครือข่ายผู้เกษียณอายุราชการของกองบิน ๔๑ จังหวัดเชียงใหม่ - สุกาญจน์ ยะสะวุฒิ (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2018)
The purpose of this study were (1) to study the method of creating a network and the type of retirement network. (2) to study the opportunity and possibility of creating the retirement network for Wing 41 Chiang Mai. (3) to study the strengths and weaknesses of creating the retirement network for Wing 41 Chiang Mai. The results of this study were (1) the Wing 41 retirees have suggested the method of creating the retirement network as the advisor for Wing 41 officers, that there should be some inspirations for the retirees and also their opinions should be considered. (average = 4.05) In addition, the status of the members should be equal as the partnership status. It should be more horizontal relationship than the boss and staff relationship. (average = 4.01). The network should initially be started informally from the high commanders of each department for instance, civil engineer department, communication department, aeronautical engineer department, and medical department, etc .(average =3.88) The feature of the network should be either individual, group or formal organization or semi-formal organization such as club, association and committee in order to get the acceptance. (average = 3.86) (2) There is high possibility for developing the retirement network for Wing 41 Chiang Mai since Wing 41 has a very significant motivation strategy to bring the skillful retirees back to work for the air force. It is also beneficial for the air force as they can be the best knowledge source. Also they are willing to join and devote themselves for wing 41. Additionally, they get a great deal of support from Wing 41 officers. (3) The strengths of creating the retirement network for Wing 41 Chiang Mai are: The retirees can be the good advisor for Wing 41 personnel both technically and academically. Their experiences can be make the wing 41 officers develop their potentials in order to use the strengths of the retirees to fullfill the weaknesses of present officers . Also, the retirees can be the knowledge source for Wing 41 development. However, the weaknesses are: wing 41 officers may have difference attitudes or aspects to problems and needs that can make them sprit up. In addition, The retirement network can affect the morale of wing 41 officers and give the retirees a chance to interfere with the current work.